Pediatric Meckel's diverticulum: Experience from a tertiary center in Eastern India - Debashree Priyadarshini; O.Y. Pavan K Reddy; Rachita Sarangi; Antaryami Pradhan (Amaltea Medical Publishing House, 2023)
Background. Meckel's diverticulum (MD) is the most common congenital anomaly of the gastrointestinal tract, having a varied clinical presentation in the pediatric age group. It can manifest with life-threatening complications when symptomatic. However, very few studies have been reported from Eastern India. In this study, we aim to analyze the demographics, clinical presentation, associated characteristics, laboratory and histopathological features, various modalities of diagnosis, and treatment for pediatric Meckel's diverticulum. Results. 18 children were diagnosed with Meckel's diverticulum. Children below five years of age accounted for the majority of cases, with almost 50% presenting before age two. A male predominance was seen in the study with a male-tofemale ratio of 4:1. The presentation was usually acute with lower gastrointestinal bleeding being the most common symptom in our study. Open diverticulectomy was the most common surgical procedure performed. MD was found on the mesenteric surface of the distal ileum in two cases. Simultaneous endo colon (upper GI endoscopy & colonoscopy) followed by laparoscopic surgery was done in a single setup in two actively bleeding cases with negative Meckel's scan. There was no mortality, and no complications were noted on follow-up. Conclusion. MD had an acute presentation with lower GI bleeding being the commonest presenting symptom. It can be found on the mesenteric surface of the distal ileum. Open diverticulectomy was the treatment of choice for symptomatic patients. Surgical removal of incidentally detected MD was not associated with adverse outcomes.